ON GOD AND BOUNDARIES: T.T. CLOETE’S TRISTETRAHEDRONIS AS A MODEL OF EXPANDING BOUNDARIES - Robinson, Rensia (Scriptura, 1997)
The significance and the possibilities of defining borders as a means to create perspective of what lies beyond limitation can be introduced through poetic strategies. In a volume of poetry names ‘Driepas’ (1989), the poet T.T. Cloete explores the signification of tripartite forms in nature, in science, in art and as symbols in places of worship. This voyage of discovery concentrates in a poem under the title Tristetrahedronis (‘Driepas’ 1989:160).